Fundamentals of applied probability and random processes - Ibe Oliver C (Amsterdam Elsevier, 2005)
This book is based on the premise that engineers use probability as a modeling tool, and that probability can be applied to the solution of engineering problems. Engineers and students studying probability and random processes also need to analyze data
Keywords: Probabilities; Random processes